The Tidal Disruption Event AT 2018hyz II: Light-curve modelling of a partially disrupted star. Issue 2 (20th July 2020) - Gomez, Sebastian; Nicholl, Matt; Short, Philip; Margutti, Raffaella; Alexander, Kate D; Blanchard, Peter K; Berger, Edo; Eftekhari, Tarraneh; Schulze, Steve; Anderson, Joseph; Arcavi, Iair; Chornock, Ryan; et al.
ABSTRACT: AT 2018hyz (= ASASSN-18zj) is a tidal disruption event (TDE) located in the nucleus of a quiescent E+A galaxy at a redshift of z  = 0.04573, first detected by the All-Sky Automated Survey for Supernovae (ASAS-SN). We present optical+UV photometry of the transient, as well as an X-ray spectrum and radio upper limits. The bolometric light curve of AT 2018hyz is comparable to other known TDEs and declines at a rate consistent with a t −5/3 at early times, emitting a total radiated energy of E  = 9 × 10 50  erg. An excess bump appears in the UV light curve about 50 d after bolometric peak, followed by a flattening beyond 250 d. We detect a constant X-ray source present for at least 86 d. The X-ray spectrum shows a total unabsorbed flux of ∼4 × 10 −14  erg cm −2 s −1 and is best fit by a blackbody plus power-law model with a photon index of Γ = 0.8. A thermal X-ray model is unable to account for photons >1 keV, while a radio non-detection favours inverse-Compton scattering rather than a jet for the non-thermal component. We model the optical and UV light curves using the Modular Open-Source Fitter for Transients (MOSFiT ) and find a best fit for a black hole of 5.2 × 10 6  M⊙ disrupting a 0.1 M⊙ star; the model suggests the star was likely only partially disrupted, based on the derived impact parameter of β = 0.6. The low optical depth implied by the small debris mass may explain how we are able to see hydrogen emission with disc-like line profiles in the spectra of AT 2018hyz (see our companion paper).